2019
DOI: 10.1159/000499085
|View full text |Cite
|
Sign up to set email alerts
|

Moderator Effects of Life Stress on the Association between MAOA-uVNTR, Depression, and Burnout

Abstract: Background: The serotonergic and noradrenergic systems have a strong impact on several affective disorders and are key targets for psychopharmacological therapy. With respect to pathogenesis, there is a growing body of evidence showing an influence of a promoter repeat polymorphism (MAOA-uVNTR) altering the expression rate of monoamine oxidase A. However, only a few studies investigate its influence on depression with only 2 of them considering the moderating effects of life stress. For burnout, there are no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Catecholamine import and degradation by OCT3 and MAO-A determine the local concentration, duration, and physical spread of released catecholamines, critically modulating the magnitude, duration, and diversity of their effects in physio(patho)logical conditions [ 20 ]. Given their role in modulating neurotransmitters, MAO-A and OCT3 in the brain are also pathogenic factors of depressive disorders [ 11 , 33 , 35 , 42 , 51 ]. Here, we found elevated cardiac catecholamine levels in cardiac-specific MAO-A knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamine import and degradation by OCT3 and MAO-A determine the local concentration, duration, and physical spread of released catecholamines, critically modulating the magnitude, duration, and diversity of their effects in physio(patho)logical conditions [ 20 ]. Given their role in modulating neurotransmitters, MAO-A and OCT3 in the brain are also pathogenic factors of depressive disorders [ 11 , 33 , 35 , 42 , 51 ]. Here, we found elevated cardiac catecholamine levels in cardiac-specific MAO-A knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…We then multiplied each “yes” answer with its intensity rating and summed all resulting scores to get a single cumulative life stress score for each participant. The SLE list has already been used in other studies and has been shown to be associated to depressive and – to a lesser degree - burnout symptomatology (Plieger et al, 2019; Plieger, Melchers, Montag, Meermann, & Reuter, 2015) (see supplementary material available from https://osf.io/q57pk/ for the complete item list).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that individuals with MAOA-L may be at increased risk of depletion of an HPA response under stress [17]. Male carriers of MAOA-H have a larger dopamine release and elevated aggression after a violent movie [18], whereas female carriers have higher scores on both burnout and depression after stressful life events [19]. In female 3R carriers, there is higher emotional stability, which negatively correlates with depression and anxiety [20].…”
Section: Introductionmentioning
confidence: 99%